(untitled) (Texas Journal of Medical Science, 2024)
This article is a study aimed at analyzing and improving the results of surgical treatment of patients with hip fractures in concomitant injuries using modern technologies. Within the framework of the study, the results of treatment of 233 patients with concomitant hip injuries were analyzed, a surgical method - osteosynthesis was used. early period of a traumatic disease. The results of the study made it possible to determine the optimal methods of fixation depending on the patient’s condition. The findings of this study are important for improving the results of surgical treatment of patients with concomitant hip injuries and can be used in practical medicine to optimize treatment tactics and reduce complications